External Determinants of the Development of Small and Medium-Sized Enterprises – Empirical Analysis - Renata Lisowska (Journal of Entrepreneurship, Management and Innovation)

(untitled)
The paper aims to identify external determinants of the development of small and medium-sized enterprises and assess their impact on the functioning of these entities in Poland. Meeting this objective required: identifying determinants of the development of SMEs, determining the current development situation of the surveyed enterprises and examining the impact of external determinants on the development of SMEs. The implementation of the above-presented goals was based on the following assumptions: (i) the current situation of the surveyed enterprises is determined with the use of quantitative indicators (turnover volume, number of employees, market share, profit levels) (ii) the analysis of external determinants encompasses three components of the environment: the macro-environment, the meso-environment and the micro-environment, (iii) in each analysed area there are separate analyses conducted for micro, small and medium-sized enterprises, enabling greater precision in the identification of external determinants of development for each category of businesses.